Customs and Finance Management of Mahabad City, in the Light of Documents - حەکیم‌ زادە, فەرەیدون (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The main purpose of this paper concerned with the review and survey of the role of custom management in Kurdistan republic (1946) government. To achieve this goal, by a historical approach, methods such as analytical-descriptive, text analysis and documentary analysis were used. This research includes four main topics, namely conditions of Mahabad city from 1942 to 1947; establishment of the Kurdistan republic in 1946; showing several historical documents about living of local people and analysis of custom office in the Kurdish government in Mahabad. The research findings suggest that Customs and its revenue were very important at that time as a result the authorities of the Republic of Kurdistan more or less have paid attention to this economic center; so, in this regard, they have adopted various strategies for example Economic development of the region with the aim of self-sufficiency and back up local products such as wheat, barley and tobacco. Controlling the customs office and supervising exports and imports So that they prevented the sale of domestic products outside the borders, while transactions inside the Kurdistan were encouraged by the Kurdish management.